Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
yunmathf4

# yunmathf4

Ratings: (0)|Views: 0 |Likes:
free
free

Categories:Types, School Work

### Availability:

See more
See less

08/10/2014

pdf

text

original

Chapter 1 : Standard form

Chapter 2 : Quadratic expressions and Equations

1. A quadratic expression in the form ax
2
+bx+c,wherea,b and c are constants,a≠0 and × is
an unknown. For example: (a) 3x2 - 4x + 5 (b) 2x2 + 6x (c) x2-9 2.In a quadratic expression:

there is only one unknown

the highest power of the unknown is 2
* Forming quadratic expressions by multiplying two linear expressions
1. When two linear expressions with the same unknown are multiplied,the product is a quadratic expression. 2. The multiplication process is known as expansion
* Forming quadratic expressions based on specific situations
To form quadratic expressions based on specific situations : 1.Choose a letter to represent the unknown.2.Form a quadratic expressions based on the information given.
2.2 Factorisation of quadratic expressions *Factorising quadratic expressions of the form ax
2
+ bx + c,where b =0 or c =0
1.When b = 0, ax
2
+ c can be factorised by finding the highest common factor (HCF) of the coefficients a and c.

2.When c=0,ax
2
x< + bx can be factorised by finding the highest common factor of the coefficients a and b.x is also a common factor of the two terms.
*Factorising quadratic expressions of the form px
2
- q,where p and q are perfect squares
Let p = a² and q = b² px² - q = (ax)² - b² = (ax + b) (ax - b)
*Factorising quadratic expressions of the form ax
2
+ bx + c, where a

≠ 0, b

≠ 0 and c

≠ 0

1.We can use the inspection method and cross method to factorise quadratic equations of this form. 2.Tofactorise quadratic expressions : (a) ax² + bx + c, where a = 1 x² + bx + c =(x + p) (x + p) =x² + qx + px +

=x² + (p + q) x + pq

In comparison, b = p + q ,c = pq - Find the combination of two numbers whose product is c. - Choose the number combination from step 1 whose sum is b. (b) ax² + bx + c, where a > 1 ax² + bx + c =(mx + p) (nx + q) =mnx² + mqx + npx + pq =mnx² + (mq + np) x + pq In comparison, a = mn , b = mq + np , c = pq - Find the combination of two numbers whose product is a.